Penerapan Terapi Afirmasi Positif terhadap Quality of Life pada Pasien Skizofrenia di Wilayah Kerja Puskesmas Kota Tengah, Kota Gorontalo - Biahimo, Nur Uyuun I.; Tulabu, Hasnawati (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2025)
Schizophrenia is a severe mental disorder commonly found in Indonesia. Patients with schizophrenia often experience low self-concept, poor quality of life, and a high level of stigma. The implementation of positive affirmation therapy is one form of non-pharmacological intervention that can be provided to individuals with schizophrenia. This community service activity involved the provision of positive affirmation therapy to schizophrenia patients in the working area of Kota Tengah Public Health Center, Gorontalo City. The activity was conducted in January 2025, with a total of 15 participants. The therapy was administered over three consecutive days, through direct face-to-face sessions, each lasting 45–60 minutes. A nursing standard operating procedure (SOP) was used as a guide for delivering the positive affirmation therapy. Evaluation of the therapy was conducted orally and subjectively based on participants' conditions. To assess participants’ quality of life, the WHOQOL-BREF quality of life questionnaire was used. The results of the activity showed that, prior to therapy, the majority of participants had poor quality of life (11 participants or 73.3%), while a smaller proportion had good quality of life (4 participants or 26.7%). On the third day of therapy, improvements were observed: the majority of participants (12 participants or 80.0%) reported good quality of life, while 3 participants (20.0%) still experienced poor quality of life. The implementation of positive affirmation therapy as a non-pharmacological intervention for individuals with schizophrenia can contribute to improving their quality of life. This activity also resulted in the development of a standard operating procedure (SOP) that may be used in future programs. The therapy is expected to be more effective when involving multiple stakeholders, including families and healthcare professionals, to foster collaboration in supporting schizophrenia patients to enhance their quality of life and reintegrate into social life. Achievement of Sustainable Development Goals (SDGs) This community service activity focuses on providing non-pharmacological therapy in the form of positive affirmations to outpatients with schizophrenia. The activity contributes to the achievement of SDG Goal 3, which aims to ensure healthy lives and promote well-being for all at all ages. Specifically, it aligns with Target 3.4, which seeks to reduce by one third premature mortality from non-communicable diseases through prevention and treatment, and promote mental health and well-being by the year 2030.